Education on Identification of Drug Expiration Dates and Calculation of Beyond Use Dates for Outpatient Pharmacy Installation Patients at RSKB Heart and Sugery Hospital, Bangkalan Regency - Nurus Shubuh; Nai’matul Retno Faizah; Octaviana Dyah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the effectiveness of education on identifying drug expiration dates and calculating the Beyond Use Date (BUD) among outpatients at the Pharmacy Installation of RSKB Heart and Surgery Hospital, Bangkalan Regency. The results showed that patients’ understanding before receiving education was relatively low, particularly in distinguishing between the Expiry Date and Beyond Use Date, reading expiration labels, and recognizing the risks of using expired medications. After the educational intervention, which included counseling sessions and informational leaflets, there was a significant improvement in patient understanding. This was supported by the Wilcoxon Signed Rank Test results, showing a significance value of 0.000 (< 0.05), indicating a meaningful difference in comprehension before and after the intervention. These findings align with previous studies (Ainni et al., 2024; Iskandar et al., 2022; Rosanti et al., 2023), which also demonstrated the effectiveness of education through counseling, discussions, and media such as leaflets in enhancing public and patient knowledge about drug expiration and BUD. Therefore, regular pharmaceutical education plays a crucial role in improving patient awareness and medication safety, particularly in understanding expiration and BUD calculations, thereby helping to prevent the use of unsuitable drugs and enhancing patient safety.